A review of implementation and evaluation frameworks for public health interventions to inform co-creation: a Health CASCADE study - Giuliana Raffaella Longworth; Kunshan Goh; Danielle Marie Agnello; Katrina Messiha; Melanie Beeckman; Jorge Raul Zapata-Restrepo; Greet Cardon; Sebastien Chastin; Maria Giné-Garriga (BMC, 2024)
Abstract Background By including the needs and perspectives of relevant stakeholders, co-creation is seen as a promising approach for tackling complex public health problems. However, recommendations and guidance on how to plan and implement co-creation are lacking. By identifying and analysing existing implementation and evaluation frameworks for public health, this study aims to offer key recommendations for professional stakeholders and researchers wanting to adopt a co-creation approach to public health interventions. Methods Firstly, PubMed and CINAHL databases were screened for articles introducing original implementation and evaluation frameworks for public health interventions. Backwards snowballing techniques were applied to the included papers. Secondly, identified frameworks were classified and relevant data extracted, including steps and constructs present in the frameworks. Lastly, recommendations were derived by conducting thematic analysis on the included frameworks. Results Thirty frameworks were identified and data related to their nature and scope extracted. The frameworks' prominent steps and constructs were also retrieved. Recommendations related to implementation and evaluation in the context of co-creation were included. Conclusion When engaging in co-creation, we recommend including implementation considerations from an early stage and suggest adopting a systems thinking as a way to explore multiple levels of influence, contextual settings and systems from an early planning stage. We highlight the importance of partnering with stakeholders and suggest applying an evaluation design that is iterative and cyclical, which pays particular attention to the experience of the engaged co-creators.